University - Hopkinson, Alan (Infotheca - Journal for Digital Humanities; Vol 5 No Special is (2004): Infotheca - Journal of Informatics and Librarianship, 2024)
Middlesex University takes staff development more seriously than many similar institutions. Information and Learning Resource Services probably even more so. Middlesex University also has annual appraisals with intermediate mini-appraisals where managers discuss staff training requirement. ILRS has a staff development group with representatives (from different management levels) from different units